Efficient Cesium Lead Halide Perovskite Solar Cells through Alternative Thousand‐Layer Rapid Deposition. (16th August 2019) - Lin, Hung‐Yu; Chen, Chien‐Yu; Hsu, Bo‐Wei; Cheng, Yu‐Lun; Tsai, Wei‐Lun; Huang, Yu‐Ching; Tsao, Cheng‐Si; Lin, Hao‐Wu
Abstract: The novel growth of cesium lead halide perovskite thin films, which are prepared through thousand‐layer rapid alternative deposition, is performed by developing an active perovskite film consisting of a layer‐by‐layer structure. This method is considerably more difficult to be implemented from the solution process. The obtained thin film morphology and characteristics are distinguished from that of the traditional a few layers and two‐material codeposition. These alternative deposited perovskites are integrated with vacuum‐deposited carrier‐transporting layers and electrodes, and all vacuum‐sublimed perovskite solar cells exhibit an outstanding power conversion efficiency of 13.0%. The use of these devices for environmental light energy harvesting provides a power conversion efficiency of 33.9% under fluorescent light illumination of 1000 lux. Abstract : Rapid alternative deposition provides new approaches for Cs‐based perovskite fabrication. The thousand‐layer CsPbI2 Br thin films obtained through this method exhibit a smooth surface and high crystallinity, and the solar cell devices deliver excellent performance under both 1‐sun solar and fluorescent light illumination.